Analisis Kinerja Saham Jii Sebelum Dan Selama Pandemi Pada Portofolio Optimal Pendekatan Model Index Tungga - Bimantoro, Krisetio; Herawati, Aty (Fakultas Ekonomi Universitas Gresik, 2023)
Forming a portfolio in investing aims to maximize the expected return with a certain level of risk. This research focuses on building an optimal portfolio of Jakarta Islamic Index (JII) stocks using a single index model before and during the pandemic. The results of the study obtained 6 stocks that were included in the optimal portfolio criteria before the pandemic, namely MIKA, BRPT, MNCN, TPIA, EXCL, WIKA. Meanwhile, during the pandemic, 15 stocks were obtained that were included in the optimal portfolio criteria, namely EMTK, BRIS, ANTM, ERAA, TINS, ITMG, ADRO, INCO, KLBF, UNTR, INKP, TKIM, JPFA, EXCL, PTBA. The results of the analysis show that there is no significant difference in the performance of JII stocks forming the optimal portfolio before the Covid-19 pandemic and during the Covid-19 pandemic as measured using the Sharpe and Treynor ratios. Meanwhile, the Jensen ratio shows that there is a significant difference in performance.